ENTREPRENEURSHIP AND INNOVATION AND SOCIAL ENTREPRENEURSHIP IN VIETNAM: AN EXAMINATION FROM INSTITUTIONAL AND IDEOGRAPHIC LENS - Quan Vu Le; Yolanda Sarason (Tạp chí Khoa học Đại học Đà Lạt)
This paper is an introduction to the special issue of Dalat University Journal of Science – Economics and Management on entrepreneurship in Vietnam. There are four papers in this special issue. The first paper examines the impact of institutions on entrepreneurship using data from the Provincial Competitive Index. The second paper utilizes a different set of institutional indicators from the World Bank’s Vietnam Enterprise Survey to assess the impacts of business environment on the development of SMEs. In both papers, the authors find that institutional factors such as entry barriers, lack of policy support systems, informal payment, provincial leadership, lack of access to finance, administrative and procedures, and tax inspections hindered the development of entrepreneurship in Vietnam. The third paper investigates the absence of medium-sized enterprises and the necessity for the development of such enterprises is critically important for Hochiminh City. Using primary and secondary data sources, the author presents a case study on two strategic sectors in the city. The result indicates that medium-sized enterprises are proven to be more effective than large-scale enterprises. The last paper focuses on social entrepreneurship in Vietnam. The authors use Hofstede’s measure of cultural differences to compare social ventures in Vietnam and the United States.